2010
DOI: 10.3144/expresspolymlett.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of sepiolite on intumescent flame retardant polypropylene

Abstract: Abstract. In this paper, the effects of sepiolite as a synergistic agent on the flame retardancy of intumescent flame retardant polypropylene (PP/IFR) were studied using the limiting oxygen index (LOI), the UL-94 test, thermogravimetric analysis (TGA), laser Raman spectroscopy (LRS), cone calorimeter test (CCT) and scanning electron microscopy (SEM), and the IFR system mainly consisted of the ammonium polyphosphate modified with γ-aminopropyltriethoxysilane coupling agent, melamine and dipentaerythritol. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 43 publications
(48 reference statements)
1
49
0
Order By: Relevance
“…From the curves it can be observed that neat MPP showed one weight loss step between 400 and 500°C, while all blends displayed an additional degradation step in the 200-300°C temperature range. This additional weight loss process has been attributed to the decomposition of the additives initiated by thermal dehydration reactions, as confirmed by massive water evolution detected through mass spectrometry [11]. This step appeared at a slightly lower temperature in B15 with respect to the other blends, probably due to its higher content of -OH groups.…”
Section: Dynamic Mechanical Thermal Morphological and Mechanical Promentioning
confidence: 91%
“…From the curves it can be observed that neat MPP showed one weight loss step between 400 and 500°C, while all blends displayed an additional degradation step in the 200-300°C temperature range. This additional weight loss process has been attributed to the decomposition of the additives initiated by thermal dehydration reactions, as confirmed by massive water evolution detected through mass spectrometry [11]. This step appeared at a slightly lower temperature in B15 with respect to the other blends, probably due to its higher content of -OH groups.…”
Section: Dynamic Mechanical Thermal Morphological and Mechanical Promentioning
confidence: 91%
“…[1][2][3] Nevertheless, IFR's relatively low flame retardant efficiency impedes their actual commercial applications. To overcome this disadvantage, many synergists, including zeolites, [4,5] iron powder, [6] fumed silica, [7] rare earth oxide, [8] sepiolite, [9] ultrafine full-vulcanized powdered rubber, [10] montmorillonite (MMT), [11] etc., have been introduced to improve the flame retardant efficiency of IFR.…”
Section: Introductionmentioning
confidence: 99%
“…Among the synergistic agents, silicate has attracted great attention in recent years because of its low cost, easy availability and high efficiency. Up to now, the study on synergistic effects of silicate have mainly focuses on montmorillonite, kaolin, sepiolite and silica, [5][6][7][8][9][10][11][12] but little investigation has been made on vermiculite (VMT). [13] The VMT is a 2:1 layer type of the mica group silicates which consists of octahedrally coordinated cations, typically Mg, Ca, Al, and Fe, sandwiched by tetrahedrally coordinated cations, typically Si and Al.…”
Section: Introductionmentioning
confidence: 99%